2011
DOI: 10.5301/jva.2011.6278
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Electrospun Polycarbonate-Urethane Vascular Graft for Early Hemodialysis Access: First Clinical Results in Man

Abstract: The electrospun polycarbonate-urethane graft is safe in humans, permits early access obviating the need for venous catheters, and has equivalent patency to other prosthetic grafts at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Its composition and form is hypothesized to be more biocompatible, which is expected to increase patency rates due to lower graft stenosis, and exhibit shorter times for cannulation due to better resealing properties [13]. However, a clinical study of AVflo showed that patency rates were similar to values reported for ePTFE grafts [14]. Future clinical studies will need to measure the advantage of shortened cannulation time for AVflow compared with existing grafts given that patency rates were not improved si gnificantly.…”
Section: Clinical Applications For Electrospinning In Drug Deliverymentioning
confidence: 90%
See 1 more Smart Citation
“…Its composition and form is hypothesized to be more biocompatible, which is expected to increase patency rates due to lower graft stenosis, and exhibit shorter times for cannulation due to better resealing properties [13]. However, a clinical study of AVflo showed that patency rates were similar to values reported for ePTFE grafts [14]. Future clinical studies will need to measure the advantage of shortened cannulation time for AVflow compared with existing grafts given that patency rates were not improved si gnificantly.…”
Section: Clinical Applications For Electrospinning In Drug Deliverymentioning
confidence: 90%
“…AVFlow TM (Nicast) [13,14] Polyurethane Composite vascular graft Implant PK Papyrus (Biotronik) [12] Polyurethane Coating metal stent Implant…”
Section: Commercial Productsmentioning
confidence: 99%
“…Furthermore, the PCU was chosen because it is widely used for the fabrication of implantable devices (i.e. vascular grafts, artificial heart components) [38,39] and for all the biomedical applications that require high biocompatibility and a superior mechanical response in terms of elongation, flexibility, and chemical stability under aggressive microenvironments [40]. This is due to the presence of strong intermolecular bonds with polycarbonate polyol, which makes them highly resistant to biodegradation and hydrolysis [41].…”
Section: Materials Methods and Instrumentationmentioning
confidence: 99%
“…The AVflo is a CE-certified electrospun nanofibrous-based polyurethane vascular access graft developed by Nicast Ltd, Israel, which is currently available in Asian countries, European Union market, and Israel [15]. The clinical trial studies of AVflo were conducted in patients and well reported [16]. The company is in further progress of developing nanofiber-based products such as nanostructured bioactive small-diameter vascular graft, biodegradable implant toward a better therapy for visual sensory impairments, biomimetic nanofiber-based nucleus pulposus regeneration for the treatment of degenerative disk disease, and NovaMesh Ventral Hernia Mesh.…”
Section: Clinical Studies In Humanmentioning
confidence: 99%